Seroepidemiology of hepatitis E in mental retardation in Birjand city in 2017 - Zohreh Azarkar; Arezou Haghdoust; Gholamreza Sharifzadeh; Negin Parsamanesh (مجله دانشگاه علوم پزشکی بیرجند, 2018)
Background and Aim: Hepatitis E is a viral disease transmitted through contaminated water, which is most commonly reported as an epidemic. Mental retardation among high-risk groups are at high risk of infection, Therefore, the present study was designed and conducted to evaluate the seroepidemiology of hepatitis E in mentally retarded individuals. Materials and Methods: This cross-sectional descriptive-analytic study was performed on 300 clients in Birjand and they were selected by the census. The Diapro Anti-Hev-IgG kit was used in this study. Data were collected by SPSS software (revision 19) and descriptive statistics were analyzed by Chi-square and Mann-Whitney tests at the level of α: 0.05. Results: Of the 300 individuals selected, a total of 267 subjects were included: 180 (67.5%) male and 87 (32.5%) female were included in the study, 62 of which (23.1%) had E-positive hepatitis and 205 (76.5%) had E-negative hepatitis. The results of the study showed that there was no significant relationship between sex and positive serology of hepatitis E, but there was a direct correlation between age and age of entering the center with positive hepatitis E serology(P=0/001). Also, the relationship between hepatitis E serology and duration of stay in the center was not significant (P = 0/27). Conclusion: The high prevalence of hepatitis E in mentally retarded individuals is alarming and emphasizes the need for appropriate screening and hygiene strategies.